Civil Society from Historical to Contemporary Perspectives - Kastrati, Ardian (European Journal of Multidisciplinary Studies, 2016)
Many scholars think that because of its ambiguous nature the definition of the civil society concept sometimes is meaningless. Civil society belongs to a group of sociological and political theory concepts such as freedom, justice, equality and democracy that are not clearly demarcated. At least two specific dimensions of the civil society concept are distinguishable: the theoretical and the normative role. In the context of theoretical role the concept of civil society analyzes dimensions of social life and social values, with citizens and civil organizations as key actors. The normative role serves to motivate and mobilize citizens and other social actors for the establishment and development of various contents and forms of civil activities. The normative function is mostly manifested during periods of transition from less to more democratic societies. Both dimensions of the civil society concept have played significant roles, especially in countries where the position of civil society has traditionally played a marginal role. Discussing the concept of civil society is quite fashionable today. Civil society is a popular term with politicians, academics and international agencies. We frequently hear politicians talk about the needs of the state and the market for a civil society. As a result, a number of authors and social and political theorists have stressed its critical importance in the processes of democratic change. The concept of civil society has been defended in various ways by a variety of political and social theorists. Today’s content of civil society does not result with a commonly accepted definition of the term, but focuses on whether the term should be a normative or non-normative tool of social science, and whether economic, religious and family relations should be considered as part of it. This paper will focus on the various meanings of civil society; a tentative definition on civil society will be introduced as well as various existing discourses of civil society.